2012
DOI: 10.3748/wjg.v18.i31.4150
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting CA19-9 values to predict malignancy in obstructive jaundice: Influence of bilirubin and C-reactive protein

Abstract: The present study proposes CRP as a new and useful correction factor to improve the diagnostic value of the CA19-9 tumor marker in patients with cholestatic jaundice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 19 publications
0
44
1
2
Order By: Relevance
“…However, CA19-9 is increased not only in patients with pancreatic or biliary cancers but also in benign biliary diseases, such as cholestasis and obstructive jaundice, resulting in misleading false positive results [23, 24]. For this reason, there is the potential for increased serum CA19-9 levels in patients with DCC, in whom the preoperative biliary drainage is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, CA19-9 is increased not only in patients with pancreatic or biliary cancers but also in benign biliary diseases, such as cholestasis and obstructive jaundice, resulting in misleading false positive results [23, 24]. For this reason, there is the potential for increased serum CA19-9 levels in patients with DCC, in whom the preoperative biliary drainage is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Another confounding factor is C-reactive protein, one of the markers of inflammation, which could also affect the CA 19-9 level. 10 In this regard, the present study excluded a confounding factor like inflammation due to surgical resection and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also suggested that the cut-off value was 90 U/mL, and specificity and sensitivity were 80-90% and 60-70%, respectively. 10,29 We determined the cut-off value of CA 19-9 level as 38 U/mL after biliary drainage, and this cut-off value was almost equal to the normal reference level, 37 U/mL. Sensitivity and specificity were 62% and 88%, respectively, after biliary drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 We and others have also suggested that this correction may slightly improve the relationship between CA 19-9 level and extent of disease in pancreatic cancer. 13ã 15 In the current issue of Annals of Surgical Oncology, Hartwig et al 16 add to the literature with one of the largest series of patients (more than 1,500) that again demonstrates that elevated CA 19-9 is associated with advanced/unresectable pancreatic adenocarcinoma despite preoperative radiologic studies demonstrating resectability.…”
mentioning
confidence: 99%